Bandit [videorecording (DVD)] - Wenman, Kraig (Kraig X.), 1980-; Duhamel, Josh, 1972-; Cuthbert, Elisha; Carbonell, Nestor, 1967-; Temmel, Swen, 1991-; D'Abo, Olivia; Gibson, Mel; Knuckle, Robert, 1935- (Quiver Distribution, 2022)
After escaping a Michigan prison, a charming career criminal assumes a new identity and goes on to rob a record 59 banks and jewelry stores while being hunted by a police task force.